Structural, magnetic and electrical properties of (La1-x Inx) 2/3 Ca 1/3 Mn03) / Abdullah Chik … [et al.] - Chik, Abdullah; Halim, S. A.; Lim, K. P.; Hamadneh, Imad; Gebrel, Z.; Dalimin, M.N. (2002)
Structural, magnetic and electrical properties of ABO3 typed (La1-xInx)2/3Ca1/3MnO3 were studied using X-ray diffractometer, AC susceptometer and DC four probe systems. Substitution of x = 0.0,0.1, 0.2, 0.3, and 0.4 were prepared using the solid-state reaction method. The metal to insulator temperature Tp and the Curie temperature, Tc, decreases as the Indium content increases showing the decreasing of ferromagnetic properties of the compound. For each substitution, there is an enhancement in susceptibility as the field intensity increases from 0.1 Oe to 10 Oe. For x = 0.4, the ac susceptibility shows a cusp around 53 K, suggesting the presence of spin glass state.